NIR-emissive, singlet-oxygen-sensitizing gold tetra(thiocyano)corroles. Issue 35 (15th August 2022) - Sahu, Kasturi; Angeloni, Sara; Conradie, Jeanet; Villa, Marco; Nayak, Manisha; Ghosh, Abhik; Ceroni, Paola; Kar, Sanjib
Abstract : Tetra(thiocyano)corrolato-Au(iii ) derivatives exhibit NIR phosphorescence under ambient conditions with emission maxima around 900 nm, phosphorescent lifetimes of 10 μs, and singlet oxygen sensitization with a quantum yield of around 50 ± 5% in solution. Abstract : Presented herein are two fully characterized gold tetrathiocyanocorroles representing a potentially significant new class of NIR-emissive 5d-metallocorroles. The four SCN groups on the bipyrrole unit of the corrole exert a powerful electron-withdrawing effect, upshifting both the oxidation and reduction potentials by roughly half a volt relative to their unsubstituted counterparts. That said, the upshift of the LUMO is somewhat higher than that of the HOMO so these complexes also exhibit a smaller HOMO–LUMO gap, as evinced in both electrochemical measurements and Q band energies (∼595 nm relative to ∼571 nm for their SCN-free counterparts). The new compounds exhibit NIR phosphorescence under ambient conditions with emission maxima around 900 nm (compared with 790 nm for simple Au triarylcorroles), phosphorescence quantum yields around 0.3%, phosphorescence lifetimes around 10 μs, and singlet oxygen sensitization with a quantum yield of around 50 ± 5% in solution, together signifying wide-ranging potential applications as triplet photosensitizers in oxygen sensing and photodynamic therapy.